Comparison Analysis of Multipath Routing Implementation in Software Defined Network - Syaifuddin Syaifuddin; Muhamad Fathul Azis; Fauzi Dwi Setiawan Sumadi (Universitas Muhammadiyah Malang, 2021)
Multipath routing is a path search method used as a data transmission process utilizing more than one available path on a network. The multipath routing concept is directed to substitute the single path routing concept for reducing network traffic congestion by distributing data transmission through several available paths. It can be implemented in the Software Defined Network (SDN) environment that separates the control plane and the data plane, which provides flexibility by deploying application-based solutions to resolve the problem. This paper is directed to implement the modified Deep First Search (DFS) multipath routing algorithm and compare the proposed method with Dijkstra and normal DFS multipath algorithm. The contribution was designed by combining the node, edge, path, and bucket weight using port statistics available in OpenFlow standard and manual calculation. The results of the system’s emulation showed that the overall algorithm could determine more than one path for the data transmission process. The average execution time on all algorithms produced 0.0903 ms for the modified DFS multipath algorithm, 0.0858 ms for DFS multipath algorithm, and 0.901 ms Dijkstra multipath algorithm, respectively. The QoS parameter testing results illustrated that the proposed method was better than another multipath routing algorithm in terms of throughput and jitter. However, based on packet loss percentage, the modified method was placed after normal DFS but still generated better results than Dijkstra. Overall, the implement multipath routing concept in SDN with all algorithms could be deployed to provide more than one data transmission path.